P-311 Comparing the impact of endometriosis vs. fibroids on women's psychological and physical health, and sexual function: a case-control study. (30th June 2022) - Dridi, D; Buggio, L; Barbara, G; Facchin, F
Abstract: Study question: What is the impact of endometriosis vs. fibroids on women's psychological and physical health, and sexual function? Summary answer: Endometriosis and fibroids are associated with worse self-perceived health status and with a greater percentage of sexual dysfunction compared with the control group. What is known already: Endometriosis and fibroids are two benign gynaecological conditions that affect a significant percentage of women globally. The negative impact of endometriosis on women's psychological health, quality of life, and sexuality has been widely demonstrated. On the other hand, the body of evidence on the impact of fibroids on women's life is smaller and with contrasting results. Recent research has demonstrated that uterine fibroids may lead to stress and poor sexual satisfaction, with a disability score similar to that of heart disease, diabetes mellitus, or breast cancer. Thus far, systematic comparisons between fibroids and endometriosis have not been addressed. Study design, size, duration: This case-control study was conducted in an Italian gynaecological clinic between March 2019 and July 2021. Sample size was determined using the software G* Power. We calculated that 252 participants were necessary to compare 3 groups using univariate analysis of variance, with a medium effect size (Cohen's f = .25), α = .05, and power = .95. Considering that the anticipated percentage of missing data was 20%, the final required sample size was 303 participants. Participants/materials, setting, methods: The study involved three groups of patients: women with diagnosed endometriosis or uterine fibroids, and women without a history of endometriosis and without fibroids (101 women in each group). All the participants completed the Hospital Anxiety and Depression Scale (HADS), the 12 item Short-Form survey (SF-12), and the Female Sexual Function Index (FSFI). A researcher made questionnaire was used to collect sociodemographic and medical information (e.g., endometriosis- and fibroid-related symptoms). Main results and the role of chance: Controlling for age, there were no significant group differences with regards to psychological health ( P =  .575). However, either women with endometriosis ( P <  .001) or fibroids ( P =  .003) reported poorer self-perceived general health status (SF-12 item 1) than women in the control group. A greater percentage of women with sexual dysfunction (FSFI total score < 26.55) was found in the two clinical groups, and especially in the endometriosis group (65%, vs 54% in the fibroids group and 44% in the control condition; χ 2 = 8.392, P =  .015). Specifically, women with endometriosis ( P <  .001) and women with fibroids ( P =  .039) reported lower desire than control participants. In addition, women with endometriosis experienced greater pain than women in the control group ( P =  .001). No statistically significant differences were found between the two clinical groups. Limitations, reasons for caution: Most of the data included in these analyses were collected during the pandemic, which has been significantly affecting people's psychological health, and especially women's emotional wellbeing. For this reason, the absence of significant group differences in the HADS score should be interpreted with caution. Wider implications of the findings: Endometriosis overall is clearly associated with sexual dysfunction, but the relation between uterine fibroids and sexual function requires further investigation, especially with regards to the effects of specific factors such as number, size and location. In general, sexual function should be routinely assessed in women diagnosed with any gynaecological condition. Trial registration number: Not applicable.